THE INFLUENCE OF ORGANIZATIONAL CULTURE, ORGANIZATIONAL COMMITMENT AND LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT PT. JAYA CENTURY ABADI SENTOSA LHOKSEUMAWE CITY - Cheptian Simamora; Sugih Arto Pujangkoro; Iskandarini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Company performance must be seen broadly by identifying the success of the organization in meeting community needs and making improvements and improving services to the community because the government's performance has led to good governance. A successful organization is an organization that has a vision and mission that is clear, measurable and can be actualized in company performance. Performance measurement covers various aspects so that it can provide efficient and effective information in achieving performance. Measuring company performance cannot be separated from the performance of its employees. By doing their work, employees produce something called output. Performance is the result of work carried out by employees or real behavior that is reflected in their role in the organization as the organization has one goal, namely seeking profit. The organization can act on the activities or actions of the organization's employees.From previous research observations, it is also known that the phenomenon that occurs in organizations is that there is still a lack of role models for managers in terms of entering and leaving work on time, so this has become a culture or tradition among employees because many employees are not punctual, making employee performance not optimal.